Phytoconstituents evaluation and antimicrobial efficacy of the crude flavonoids and saponins rootbark extracts of Terminalia avicennioides and Ficus polita - Hamidu Usman; Abubakar U Kaigama; Olajide O Ibisagba; Ali M Fulata; Ibrahim A. Ahmed (Shahrekord University of Medical Sciences, 2018)
Introduction: Plant is a friend to man in survival as it gives him food, shelter and medicine beyond the ages of human civilization. This paper evaluates the phytochemical constituents and the antimicrobial activities undertaken on Terminalia avicennioides and Ficus polita. Methods: Phytochemical screening was conducted on the root extracts according to the standard procedures. The hole-in-plate disc diffusion technique was used to determine the antimicrobial activities of the crude saponins and crude flavonoids against the tested microorganisms used in this study. Results: The results revealed the presence of alkaloids flavonoids, saponins, sterols, phlobatannins and terpenoids. The antimicrobial activities presented as diameter of inhibition zones showed high activity value of 34.70±0.57 mm against Staphylococcus aureus and Pseudomonas aeruginosa at a concentration of 100 mg/mL and by crude flavonoids portion of T. avicennioides while the least activity was shown by crude saponins portion of F. polita at a concentration of 25 mg/mL with value of 9.67±0.58 mm against Shigella dysenteriae. The crude flavonoids inhibited the growth of Candida albicans at all concentrations while resisitances were found towards the crude saponins portion of both plants. Hence, flavonoids extractives from the two plants appeared to be more effective than the saponins against the tested microorganisms. Conclusion: These findings justify their potential use as drug-plant against bacterial-related infections in African traditional medical system and also suggest a possible insight for the isolation of bioactive chemotherapeutic agents from T. avicennioides.